EFEKTIVITAS PENGGUNAAN MEDIA AUDIO VISUAL DENGAN VIDIO MELALUI PROYEKTOR UNTUK MENSTIMULASI MOTORIK KASAR MELALUI GERAKAN SENAM SEHAT CERDAS CERIA PADA ANAK USIA DINI DI PAUD RIYADUL ULUM KELOMPOK B - Wahyudin; Dede Sulaeman; Ai Tati Nurhayati (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
The usefulness of employing audio-visual materials with video through a projector to promote gross motor abilities in early childhood through intelligent, fun, and healthy gymnastics movements serves as the driving force behind this research (descriptive study at PAUD Riyadul Ulum Group B). The purpose of this study is to better understand the gymnastics exercises that are frequently conducted by teachers and students utilizing audio-only materials and giving the pupils the task of mimicking the teacher's movements. 1) Understanding how to employ audio-visual media with video through a projector to enhance gross motor skills through healthy, intelligent, joyful gymnastics movements in early children at Riyadul Ulum PAUD is the main goal of this research. 2) Being aware of the outcomes of employing audiovisual media and video through a projector to promote gross motor abilities in young children at PAUD Riyadul Ulum Group B through healthy, clever, and joyful gymnastics routines. Students, instructors, guardians, and school principals are the topics of this study. This study is a case study-style qualitative field investigation. The findings of this study demonstrate that, in comparison to earlier research that used only audio media, the assessment of the application of audio-visual media using videos of gymnastic movements through a projector nearly met the target and was significantly successful.